A study on efficacy of mechanical bowel preparation in case of elective colorectal surgery - Madhusudan Panja; Chandranath Banerjee; Riddhisundar Samanta; Amalesh Barman (Asian Journal of Medical Sciences, 2023)
Background: There has been a resurgence of interest in the use of mechanical bowel preparation (MBP) and antibiotics before elective colorectal surgery. In the era of antibiotics, the use of MBP is controversial. Aims and Objectives: The aim of the current study was to analyze the effect of MBP over “no MBP” on outcome in patients undergoing elective colorectal surgery. Materials and Methods: This study was an institution-based prospective, randomized and comparative study. Fifty patients, who were planned for elective colorectal surgery between February 2018 and July 2019 in Department of General Surgery, were included in this study. The patients were divided into two groups. Group 1: Surgeries with use of MBP; Group 2: Surgeries without use of MBP. Outcomes of surgeries were analyzed in terms of post-operative anastomotic leak, intra-abdominal septic collections, wound infections, hospital stay, return of IPS, and start of enteral feeding. Results: This study demonstrates that risk of anastomotic leak, wound infection, intra-abdominal collection, and hospital stay were higher among MBP group over non-MBP group and also better outcomes in non-MBP groups in respect to early return of IPS, early oral feeding. Conclusion: Our study proves that no advantage is gained by preoperative MBP in elective colorectal surgery and can be easily avoided to save patients from unwanted exhaustion, distress, and adverse effects related to it.